The Comparison of Activity and Knowledge Competency between Application of the Cooperative Learning Model Make A Match Type with Discovery Learning for Class XI SMA - Fitria Anwar; Helendra Helendra; Resti Fevria; Ardi Ardi (ATRIUM PENDIDIKAN BIOLOGI, 2019)
The reason for the low competency of students' knowledge is the lack of teacher innovation when delivering learning material, so that students have not been motivated to participate and be actively involved. One way to improve the competency of students' knowledge and activities is to apply the cooperative learning model type make a match. The study aims to determine the differences in knowledge activities and competencies of students whose learning uses the cooperative model type make a match with discovery learning in students of class XI science at SMAN 7 Padang. This research is an experimental study with the research design of The Static Group Comparison Design. The study population was all students of class XI IPA 7 Padang High School who were enrolled in the first semester of the 2018/2019 academic year. Samples were taken using purposive sampling technique, where selected class XI IPA 5 as experimental I and class XI IPA 4 as experimental II. The research instrument was in the form of posttest for knowledge competencies and observation sheets for student activities. The value of the experimental I activity was (78%), higher than the experimental II (70%). Based on the test obtained the value of t count 3.12> t table 1.67, then the hypothesis is accepted. It was concluded that the activities and learning competencies of students using cooperative models of the type of make a match were better than discovery learning models.